Smartphone-based multimodal tethered capsule endoscopic platform for white-light, narrow-band, and fluorescence/autofluorescence imaging - Sharma, Gargi; Thoma, Oana-Maria; Blessing, Katharina; Gal, Robert; Waldner, Maximilian; Singh, Kanwarpal (Journal of Biophotonics, 2020)
Multimodal low-cost endoscopy is highly desirable in poor resource settings such as in developing nations. In this work, we developed a smartphone-based low-cost, reusable tethered capsule endoscopic platform that allows white-light, narrowband, and fluorescence/autofluorescence imaging of the esophagus. The ex-vivo studies of swine esophagus were performed and compared with a commercial endoscope to test the white-light imaging capabilities of the endoscope. The efficacy of the capsule for narrow-band imaging was tested by imaging the vascularization of the tongue. To determine the autofluorescence/fluorescence capability of the endoscope, fluorescein dye with different concentrations was imaged. Furthermore, swine esophagus injected with fluorescein dye was imaged using the fluorescence/autofluorescence and the white-light imaging modules, ex-vivo. The overall cost of the capsules is approximately 12 euro, 15 euro, and 42 euro for the white light imaging, the narrow-band imaging, and the fluorescence/autofluorescence imaging respectively. In addition, the cost of the laser source module required for the narrow-band imaging and the fluorescence/autofluorescence imaging is approximately 218 euro. This device will open the possibility of imaging the esophagus in underprivileged areas.
CRIS-Team WoS Importer:2020-11-27